Evaluation of Enzymatic and Chemical Treatments to Produce Oxalate Depleted Starch from a Novel Variety of Colocasia esculenta Grown in Joida, India. (20th September 2021) - Kizhakedathil, Moni Philip Jacob; Belur, Prasanna D.; Wongsagonsup, Rungtiwa; Suphantharika, Manop; Agoo, Esperanza Maribel G.; Janairo, Jose Isagani B.
Abstract: This research aimed to study granular and molecular structures, physicochemical, and functional properties of the starch extracted from a novel, dasheen type of taro conserved, and cultivated by several generations of Kunabi tribes of Joida, Karnataka, India. Further, an enzymatic (oxalate oxidase) and chemical (phosphoric acid) treatment processes are evaluated for reducing total oxalate content in the starch extracted from the taro flour. The total oxalate content of the taro flour is found to be 2344 mg 100 g −1,  and the starch yield is about 45% in all the methods. The oxalate oxidase (OxO) and phosphoric acid treatment reduced the total oxalate content by 98.37% and 98.03%, respectively. The residual oxalate content in the resultant starch is within the threshold limit (71 mg 100 g −1 ). The study of characteristic properties of enzyme‐treated (ET), phosphoric acid‐treated (PT), and native starch (NT) revealed minor changes in ET and PT compared to NT. Abstract : Oxalates are an antinutritional factor responsible for acridity, is present in taro flour. The current study aims to produce oxalate free starch by treating the taro flour with oxalate oxidase and phosphoric acid. Post treatment, the characteristic properties of the starches have been determined and compared with the native starch, to assess the changes in the structural and functional properties.